Earnings Quality Drivers: Do Firm Attributes and Ownership Structure Matter in Emerging Stock Markets? - Fahad Alrobai; Ahmed A. Alrashed; Maged M. Albaz (Risks)
This research aims to examine the drivers of earnings quality (EQ) in emerging stock markets. By testing the impact of firm attributes and ownership structures on the level of earnings quality. The research followed a mixed-method approach (qualitative and quantitative) and was conducted based on a sample of 75 listed firms in Egypt as an emerging market from 2015 to 2022. The results of the research found that each firm attribute has a mixed impact on earning quality, such as firm size (positive on persistence and no impact on consistency) and ROA (U-shape on persistence and consistency). In addition, ownership structures uniquely and dynamically impact earnings, following positive, U-shape, and N-shape. This research sheds light on the drivers of the earnings quality (firm attributes and ownership structures) in the Egyptian-listed firms and helps policymakers implement appropriate corporate governance mechanisms. Our findings in Egypt can motivate future research to further investigate the most relevant factors that explain variations in earning persistence and consistency as a dimension of financial reporting quality in other emerging markets.